American secularism : cultural contours of nonreligious belief systems - Baker, Joseph O., 1938-; Smith, Buster G. (New York : New York University Press, 2015)
A rapidly growing number of Americans are embracing life outside the bounds of organized religion. Although America has long been viewed as a fervently Christian nation, survey data show that more and more Americans identify as "not religious." American Secularism documents how changes to American society have fueled these shifts in the (non)religious landscape and examines the diverse and dynamic world of secular Americans. Baker and Smith offer a framework for understanding nonreligious belief systems as worldviews in their own right, rather than merely as negations of religion. Drawing on multiple sources of empirical data, this volume explores how people make meaning outside of organized religion, outlines multiple expressions of secular identity, and connects these self-expressions to patterns of family formation, socialization, social class, ethnicity, gender, and sexuality. Further, the authors demonstrate how shifts in secularisms reflect changes in the political meanings of religion in American culture. Ultimately, American Secularism offers a more comprehensive sociological understanding of worldviews beyond traditional religion. -- from back cover.
Introduction : A nation of nonbelievers -- Classifying secularities -- A cultural view of secularities -- Historical foundations -- The great abdicating -- Nonreligious belief systems -- Ethnicity, assimilation, and secularity -- Gender and secularity -- Marriage, family, and social networks -- The (explicit) politics of secularity -- Conclusion : A secular, cosmical movement?
Includes bibliographical references (pages 271-281) and index.
Keywords: Secularism -- United States